Strategy to Strengthen Sustainable Waste Management Policy in Lhokseumawe City Tourist Destinations (Architecture Image Studies, 2025)
Lhokseumawe City, as one of the tourist destinations in Aceh Province, faces serious challenges in waste management that are increasing along with the growth in the number of tourists and population. Although there has been a policy through Qanun Number 9 of 2015 that prioritizes the 3R principle (reduce, reuse, recycle), its implementation still encounters significant obstacles. This study aims to analyze the implementation of waste management policies in Lhokseumawe, identify the main obstacles, and formulate more effective strategies for sustainable waste management. The method used in this study is a qualitative approach with case studies, which involves in-depth interviews, participatory observations, and document analysis. The results of the study show that the main obstacles faced are weak law enforcement, limited waste management facilities, and lack of active community participation. In addition, the lack of adequate budget and infrastructure also exacerbates this situation. Therefore, to achieve more effective waste management, it is necessary to increase the budget of the hygiene sector, improve infrastructure, as well as cross-sector collaboration and community empowerment. This research provides strategic recommendations for the Lhokseumawe City government to improve waste management policies to support tourism sustainability and the quality of the city's environment.